Ecuaciones De Primer Grado
1. x + 4 = 28
X
= 28-4
X
= 24
2. y - 6.5 = 31
Y
= 31 + 6.5
Y
= 37.5
3. 8z = 40+3z
8z – 3z = 5z = 40
5z = 40
Z
= 40/5
Z
= 8
4. 10x = -5x + 60
10x + 5x = 15x = 60
15x = 60
X
= 60/15
x= 4
5. -15y + 3 = -36 - 18y
-15y + 18y= 3y = -39
3y = -39
Y
= -39/3
Y
= -13
6.
2x + 4 + (3x - 4) = 3x + 12
2x + 4 + 3x – 4 = 3x + 12
2x + 3x + 3x = 12 – 4 + 4
2x = 12
X = 12/2
X = 6
7. 4 ( 3x + 2) - 8= 5 (2x + 3) + 5
12x + 8 - 8= 10x + 15 + 5
12x - 10x= 15 + 5 – 8 + 8
2x = 20
X
= 20/2
X
= 10
8. 15x – 40 - 5x – 20 = 0
15x – 5x = 40 + 20
10x = 60
X
= 60/10
X
= 6
9. 16 - (-2x - 4) - (5x - 3x + 2) = -4x - (-8x
+ 2)
16 + 2x + 4 - 5x + 3x – 2 = -4x + 8x - 2
2x - 5x + 3x + 4x - 8x= -2 – 16 – 4 + 2
-4x = -20
X = -20/ -4
X = 5
10. - ( 7x – 2 + 12) + (-5x - 3x + 4)= -
(-x + 7) - (6x – 4 -7)
-7x + 2 – 12 -5x -3x + 4 = x – 7 - 6x + 4 +7
-7x - 5x - 3x – x + 6x= -7 + 4 + 7 -2 + 12 -4
-10x = 10
X = 10/-10
X = -1
11. -18 - [3(x + 2) + 4] = 21 - [6 (-2x -2)
+ 1]
-18 - [3x + 6 + 4] = 21 - [ -12x – 12 + 1]
-18 - 3x - 6 - 4 = 21 + 12x + 12 -
1
-3x -12x = 21 + 12 -1 + 18 + 6 + 4
-15x = 60
X = 60/-15
x = -4
No hay comentarios:
Publicar un comentario